2020
DOI: 10.2147/ijn.s249511
|View full text |Cite
|
Sign up to set email alerts
|

<p>Docetaxel-Loaded Cholesterol-PEG Co-Modified Poly (n-Butyl) Cyanoacrylate Nanoparticles for Antitumor Drug Pulmonary Delivery: Preparation, Characterization, and in vivo Evaluation</p>

Abstract: Background and Aim: Polymeric nanoparticles (NPs) have received much attention as promising carrier systems in lung cancer and brain metastases. Methods: Here, for the first time, we investigated the feasibility of using inhaled cholesterol-PEG co-modified poly (n-butyl) cyanoacrylate NPs (CLS-PEG NPs) of docetaxel (DTX) for sustained pulmonary drug delivery in cancer metastasis. Results: Spray-dried or freeze-dried NPs yielded sustained drug release in vitro. In vitro inhalation evaluation data indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The particles’ aerodynamic assessment indicated 4.20 μm of MMAD with a geometric standard deviation (GSD) of 4.44 and an FPF of 59.44%. The above results indicated that the use of 10% leucine in the formulation was more inhalable when administered via an inhaler …”
Section: Pulmonary Delivery Of Nanoparticlesmentioning
confidence: 71%
“…The particles’ aerodynamic assessment indicated 4.20 μm of MMAD with a geometric standard deviation (GSD) of 4.44 and an FPF of 59.44%. The above results indicated that the use of 10% leucine in the formulation was more inhalable when administered via an inhaler …”
Section: Pulmonary Delivery Of Nanoparticlesmentioning
confidence: 71%
“…Finally, there is significant variation in the volume of the release medium across literature. Some studies have utilized a very high volume (e.g., 200 mL [ 21 , 29 ]) of release medium which significantly deviates from the volume of human lung lining fluid; 10 – 30 mL is generally considered for better correlation with the clinical application of inhalable nanoparticle-based powders [ 109 ]. As with redispersibility studies, in vitro drug release studies should be performed in biorelevant media such as PBS or SLF.…”
Section: Characterization and Quality Attributes For Inhaled Dry Powdermentioning
confidence: 99%
“…Lung cancer is a major public health problem worldwide, while non-small cell lung cancer (NSCLC) represents about 80-90% of all cases (49)(50)(51)(52)(53). Indeed, NSCLC has a high mortality rate, and the 5-year survival rate of these patients remain challenging (54)(55)(56)(57).…”
Section: Lung Cancermentioning
confidence: 99%